2019
DOI: 10.1016/j.jsv.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of acoustic modes using Helmholtz and Quarter-Wave resonators tuned at exceptional points

Abstract: Acoustic dampers are efficient and cost-effective means for suppressing thermoacoustic instabilities in combustion chambers. However, their design and the choice of their purging air mass flow is a challenging task, when one aims at ensuring thermoacoustic stability after their implementation. In the present experimental and theoretical study, Helmholtz (HH) and Quarter-Wave (QW) dampers are considered. A model for their acoustic impedance is derived and experimentally validated. In a second part, a thermoacou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…The specific admittance of a non-dissipative closed duct, below its cut-on frequency (pure one-dimensional acoustic propagation), is . It was shown in § 2.1.2 of the paper from Bourquard & Noiray (2019), that asymptotically behaves, around , as , with . This approximation provides an explicit formulation of quarter wave type resonances as a second-order harmonic oscillator with equivalent mass , i.e.…”
Section: Linear Model Of Coupled Oscillatorsmentioning
confidence: 94%
“…The specific admittance of a non-dissipative closed duct, below its cut-on frequency (pure one-dimensional acoustic propagation), is . It was shown in § 2.1.2 of the paper from Bourquard & Noiray (2019), that asymptotically behaves, around , as , with . This approximation provides an explicit formulation of quarter wave type resonances as a second-order harmonic oscillator with equivalent mass , i.e.…”
Section: Linear Model Of Coupled Oscillatorsmentioning
confidence: 94%
“…EPs have been identified as the fundamental concept at the base of many scientific phenomena in several fields, including non-Hermitian quantum mechanics, optics and acoustics [16][17][18]. In thermoacoustics, they have only been recently discussed [19].…”
Section: Introductionmentioning
confidence: 99%
“…This has analogies with the EPs arising due to the acoustic coupling between a cavity and an acoustic damper. In this respect, Bourquard & Noiray (2019) experimentally demonstrated the existence of such EPs, and showed that both Helmholtz resonators and quarter-wave tube dampers achieve optimal damping performance when tuned to operate at the EPs of the closed-loop coupled acoustic system. In this study, we relate EPs in the spectrum of thermoacoustic systems with (i) the high sensitivity experienced by some thermoacoustic eigenvalues and (ii) the limits of validity of high-order perturbation methods.…”
Section: Introductionmentioning
confidence: 99%